Is it Time to Normalize Scapular Dyskinesis? The Incidence of Scapular Dyskinesis in Those With and Without Symptoms: a Systematic Review of the Literature - Paul A. Salamh; William J. Hanney; Trey Boles; Daniel Holmes; Alex McMillan; Austin Wagner; Morey J. Kolber (International Journal of Sports Physical Therapy)
# Background